Performance analysis of a multi-user outdoor visible light communication system using wavelength division multiplexing (WDM) with RZ-OOK and NRZ-OOK modulations for V2X communications - Anass Kharbouche; Hamza Ouamna; Zhour Madini; Younes Zouine (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
Vehicle-to-Everything (V2X) communication represents a revolution in traffic management and road safety, with innovation at the heart of this evolution. In this context, Visible Light Communication (VLC) emerges as a promising alternative to meet the demands for high-speed and low-latency communication. LED lamps, primarily used for lighting, can also serve as data transmission mediums. This article proposes a VLC system utilizing Wavelength Division Multiplexing (WDM) to simultaneously transmit data streams from different sources via a Free Space Optical (FSO) channel.We evaluated the performance of this system by analyzing the impact of the Return to Zero (RZ) and Non Return to Zero (NRZ) formats at the optical transmitter on the WDM/FSO system. Simulations were conducted by varying the FSO channel distance and testing different throughput scenarios while considering weather conditions. The results show that Return to Zero, On-Off Keying (RZ-OOK) modulation can achieve high data rates at short distances, while Non Return to Zero, On-Off Keying (NRZ-OOK) modulation excels at longer distances with moderate data rates, particularly under adverse weather conditions.These findings pave the way for innovative applications in the field of V2X communications, addressing the specific needs of both urban and non-urban environments.